Clasificación de enfermedades en la caja torácica por medio de radiografías (2020)
The early detection of diseases can be decisive for the life of a person. On medical environment the x-ray are used commonly for diagnosis of illness because the presence of patterns, spots and another kind of visual signals. This document shows the development of models with convolutionals networks: VGG16 and VGG19, used for creation of a binary classificator with an accuracy of 95% and a multiclass classificator with an accuracy of 85%, that catalog 4 different illness.